2010
DOI: 10.1007/s12550-010-0071-6
|View full text |Cite
|
Sign up to set email alerts
|

Precise determination of the Alternaria mycotoxins alternariol and alternariol monomethyl ether in cereal, fruit and vegetable products using stable isotope dilution assays

Abstract: Cereal, fruit and vegetable products were analyzed for contamination with the Alternaria mycotoxins alternariol (AOH) and alternariol monomethyl ether (AME) using stable isotope dilution assays (SIDAs). Both toxins were practically not detected in cereals and cereal products: AOH-one out of 13 samples at a content of 4.1 μg/kg; AME-two out of 13 samples at contents ranging between 0.2 and 0.6 μg/kg. However, if cereals for animal nutrition were analyzed, much higher values were found: AOH-five out of six sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 22 publications
4
40
0
Order By: Relevance
“…A total of 12 samples of fresh tomatoes were reported to EFSA, all of them as non-quantified. In alignment with data reported in the literature (Asam et al, 2011), AOH was quantified in diverse fruit and fruit products, with the highest values reported for 'Figs' (LB = 5.2 lg/kg, UB = 12.4 lg/kg) and 'Pears' (LB = 3.6 lg/kg, UB = 7.8 lg/kg). AOH was also reported in 'Grape juice' (LB = 0.5 lg/kg, UB = 9.2 lg/kg) and 'Pear juice' (LB = 0.4 lg/kg, UB = 2.5 lg/kg).…”
Section: Occurrence Data On Alternariol (Aoh)supporting
confidence: 86%
“…A total of 12 samples of fresh tomatoes were reported to EFSA, all of them as non-quantified. In alignment with data reported in the literature (Asam et al, 2011), AOH was quantified in diverse fruit and fruit products, with the highest values reported for 'Figs' (LB = 5.2 lg/kg, UB = 12.4 lg/kg) and 'Pears' (LB = 3.6 lg/kg, UB = 7.8 lg/kg). AOH was also reported in 'Grape juice' (LB = 0.5 lg/kg, UB = 9.2 lg/kg) and 'Pear juice' (LB = 0.4 lg/kg, UB = 2.5 lg/kg).…”
Section: Occurrence Data On Alternariol (Aoh)supporting
confidence: 86%
“…These results are potentially danger in the preparation of grape juice that had a history of Slovakia e.g., Vinea Ltd. for children. Similarly Asam et al (2011) reported that in general fruit juices showed low concentrations of alternariol and alternariol monomethylether, but higher values of both toxins were found in wine and vegetable juices. No other quantifiable concentrations for altenuene in wine, must, grape juice, edible oils, lentils and vegetables were reported (Visconti et al 1986;Ostrý et al 2007).…”
Section: Discussionmentioning
confidence: 63%
“…Samples were extracted for 30 min with 10 mL of extraction solvent (AcN, HPLC grade) using an overhead shaker. Sample extracts were briefly centrifuged (1 min, 3200xg) and pre-weighed MgSO 4 anhydrous salt (2.00 ± 0.05g) and NaCl (0.50 ± 0.05g) (fruit and vegetable juices) or Na 2 SO 4 anhydrous salt (2.00 ± 0.05 g) (tomato products) were added. Subsequently, the tubes were vortex-mixed for 30 s, placed on an overhead shaker for 15 min and centrifuged (10 min, 3200xg).…”
Section: Sample Preparation and Extraction Methodologymentioning
confidence: 99%